Evaluating the feasibility of a nurse-led complex package of care for knee pain - Nomikos, Polykarpos (2022)
Background: Non-pharmacological interventions such as education, exercise, and weight loss (if necessary) are core to the management of Osteoarthritis (OA). The role of nurses in managing symptomatic knee OA has been advocated but whether nurses can deliver such interventions as a complex package of care is unknown. The overall aim of this research was to develop and test the feasibility of a nurse-led complex intervention for knee pain comprising non-pharmacological and pharmacological components. The specific objectives of this thesis were to: